Multicentre evaluation of case volume in minimally invasive hepatectomy. Issue 4 (9th December 2019) - Viganò, L; Cimino, M; Aldrighetti, L; Ferrero, A; Cillo, U; Guglielmi, A; Ettorre, G M; Giuliante, F; Dalla Valle, R; Mazzaferro, V; Jovine, E; De Carlis, L; et al.
Abstract: Background: Surgical outcomes may be associated with hospital volume and the influence of volume on minimally invasive liver surgery (MILS) is not known. Methods: Patients entered into the prospective registry of the Italian Group of MILS from 2014 to 2018 were considered. Only centres with an accrual period of at least 12 months and stable MILS activity during the enrolment period were included. Case volume was defined by the mean number of minimally invasive liver resections performed per month (MILS/month). Results: A total of 2225 MILS operations were undertaken by 46 centres; nine centres performed more than two MILS/month (1376 patients) and 37 centres carried out two or fewer MILS/month (849 patients). The proportion of resections of anterolateral segments decreased with case volume, whereas that of major hepatectomies increased. Left lateral sectionectomies and resections of anterolateral segments had similar outcome in the two groups. Resections of posterosuperior segments and major hepatectomies had higher overall and severe morbidity rates in centres performing two or fewer MILS/month than in those undertaking a larger number (posterosuperior segments resections: overall morbidity 30·4 versus 18·7 per cent respectively, and severe morbidity 9·9 versus 4·0 per cent; left hepatectomy: 46 versus 22 per cent, and 19 versus 5 per cent; right hepatectomy: 42 versus 34 per cent, and 25 versus 15 per cent). Conclusion: A volume–outcome association existed for minimally invasive hepatectomy. Complex and major resections may be best managed in high-volume centres. Graphical Abstract: The present study investigated the impact of the hospital case volume on minimally invasive liver surgery (MILS). It was based on the prospective registry of the Italian Group of Minimally Invasive Liver Surgery and analysed 2225 patients undergoing MILS in 46 centres. The centre case volume for MILS did not influence the outcome of standard minor hepatectomies; however, it did influence the outcome of complex hepatectomies (resection of posterosuperior segments and major hepatectomies), for which low-volume centres had higher morbidity rates than high-volume centres. Size matters